Balance and Forms of Potassium under Rice-Wheat System in a 40-year-old Long-Term Experiment on Mollisols of Pantnagar - R.H. Wanjari and Pankaj Sharma, Muneshwar Singh, Shri Ram (Journal of the Indian Society of Soil Science, 2014)
A long-term fertilizer experiment is in progress on Mollisols (Pantnagar) in order to study crop response, and dynamics and balance of nutrients as one of the objectives. Soil samples were drawn after harvest of wheat of 2010-11, and analyzed for different forms of potassium (K). The apparent and actual K balance was calculated. The results revealed that both rice and wheat responded to applied N since beginning of the experiment, and to P after growing 20 rice-wheat cycles. But so far neither of the crops responded to applied K. Analysis of different forms of K in soil indicated increase in available K with respect to initial level. The change in non-exchangeable K and water soluble K was also noted but was statistically not significant. Apparent K balance study clearly demonstrated negative balance in almost all nutrient management options (control, N, NP, 50% NPK, 100% NPK, 100% NPK+ hand weeding and 150% NPK), except NPK+FYM. However, increase in total K content was found in surface layers in plots that received fertilizer K and FYM compared to fallow plot even after continuous rice-wheat cropping for 40 years. Increase in total K in surface layer ensures that in near future K will not be a limiting factor in crop production on the Mollisols of Pantnagar.